Mapeamento geomorfológico da bacia hidrográfica do Rio Mundaú - Melo, Felippe Pessoa de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
By using the techniques of remote sensing, Geographic Information System-GIS and vector and matrix data, it was possible to identify, extract information regarding Mundau River Watershed and make the necessary cartographic material for its representativity. This watershed is located in the states of Pernambuco and Alagoas, drains an area of 42,998.30 km ², of which 52.2% are in the territory of Pernambuco and 48.8% are in the territory of Alagoas. From its source to its outfall the Mundau River runs a length of 182.45 km, its main tributary is the Canhoto River with 111.29 Km. It has topographic dimensions ranging from 0 to 1030m, its steepness classes indicate the presence of six types of reliefs (Plain, slightly wavy, wavy, tightly curled, mountainous and steep). It has three types of soils (Oxisols, Entisols and clay). The predominant vegetation is tropical forest, subperenifólia and semideciduous.